Nutrient Fluxes Associated With Submarine Groundwater Discharge From Karstic Coastal Aquifers (Côte Bleue, French Mediterranean Coastline) - Bejannin, Simon; Tamborski, Joseph James; van Beek, Pieter; Souhaut, Marc; Stieglitz, Thomas; Radakovitch, Olivier; Claude, Christelle; Conan, Pascal; Pujo-Pay, Mireille; Crispi, Olivier; Le Roy, Emilie; Estournel, Claude (Frontiers in Environmental Science, 2020)
Determination of submarine groundwater discharge (SGD) from karstic coastal aquifers is important to constrain hydrological and biogeochemical cycles. However, SGD quantification using commonly employed geochemical methods can be difficult to constrain under the presence of large riverine inputs, and is further complicated by the determination of the karstic groundwater endmember. Here, we investigated a coastal region where groundwater discharges from a karstic aquifer system using airborne thermal infrared mapping and geochemical sampling conducted along offshore transects. We report radium data (223Ra, 224Ra, 228Ra) that we used to derive fluxes (water, nutrients) associated with terrestrial groundwater discharge and/or seawater circulation through the nearshore permeable sediments and coastal aquifer. Field work was conducted at different periods of the year to study the temporal variability of the chemical fluxes. Offshore transects of 223Ra and 224Ra were used to derive horizontal eddy diffusivity coefficients that were subsequently combined with surface water nutrient gradients (NO2− + NO3−, DSi) to determine the net nutrient fluxes from SGD. The estimated DSi and (NO2− + NO3−) fluxes are 6.2 ± 5.0 *103 and 4.0 ± 2.0 *103 mol d−1 per km of coastline, respectively. We attempted to further constrain these SGD fluxes by combining horizontal eddy diffusivity and 228Ra gradients. However, SGD endmember selection in this area (terrestrial groundwater discharge vs. porewater) adds further uncertainty to the flux calculation and thus prevented us from calculating a reliable flux using this latter method. Additionally, the relatively long half-life of 228Ra (5.75 y) makes it sensitive to specific circulation patterns in this coastal region, including sporadic intrusions of Rhône river waters that impact both the 228Ra and nutrient surface water distributions. We show that SGD nutrient fluxes locally reach up to 20 times the nutrient fluxes from a small river (Huveaune River). On a regional scale, DSi fluxes driven by SGD vary between 0.1 and 1.4% of the DSi inputs of the Rhône River, while the (NO2− + NO3−) fluxes driven by SGD on this 22 km long coastline are between 0.1 and 0.3% of the Rhône River inputs, the largest river that discharges into the Mediterranean Sea. Interestingly, the nutrient fluxes reported here are similar in magnitude compared with the fluxes quantified along the sandy beach of La Franqui, in the western Gulf of Lions (Tamborski et al., 2018), despite the different lithology of the two areas (karst systems vs. unconsolidated sediment).